2020
DOI: 10.1016/j.nmni.2020.100727
|View full text |Cite
|
Sign up to set email alerts
|

Phenotypic and genotypic characterization of clinical carbapenem-resistant Enterobacteriaceae isolates from Sokoto, northwest Nigeria

Abstract: Emergence and spread of carbapenemase-producing Enterobacteriaceae (CPE) are two of the major problems currently threatening global public health. In Nigeria, interest in CPE is recent. In Sokoto, northwest Nigeria, there are no data on the prevalence and mechanism underlying carbapenem resistance. In this study, we aimed to investigate the presence of clinical carbapenems-resistant Enterobacteriaceae isolates in two leading hospitals in Sokoto, northwest Nigeria. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
17
3

Year Published

2021
2021
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(27 citation statements)
references
References 38 publications
7
17
3
Order By: Relevance
“…Surprisingly, we found no evidence for carbapenemase producing genes in both our phenotypic and genomic investigations (WGS). This is in contrast to some studies on resistance in the region that reported carbapenemase genes such as bla NDM and bla OXA−181 are widespread (Jesumirhewe et al, 2017;Olalekan et al, 2020;Olowo-Okere et al, 2020;Shettima et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…Surprisingly, we found no evidence for carbapenemase producing genes in both our phenotypic and genomic investigations (WGS). This is in contrast to some studies on resistance in the region that reported carbapenemase genes such as bla NDM and bla OXA−181 are widespread (Jesumirhewe et al, 2017;Olalekan et al, 2020;Olowo-Okere et al, 2020;Shettima et al, 2020).…”
Section: Discussioncontrasting
confidence: 99%
“…The high resistance rates we recorded are in accordance with data in other reports on human and animal isolates from Nigeria and Sub-Saharan Africa (Ojo et al, 2016;Chah et al, 2018;Aworh et al, 2019;Olalekan et al, 2020;Shettima et al, 2020). Most of our isolates also carried the bla CTX−M−15 which is consistent with the increasing reports of this genotype from animal and human sources in Nigeria (Chah et al, 2018;Okpara et al, 2018;Olowo-Okere et al, 2020). There is thus growing evidence that this genotype is expanding rapidly and might become the dominant mechanism mediating resistance to the β-lactams.…”
Section: Discussionsupporting
confidence: 91%
See 1 more Smart Citation
“…In one study, surveillance in 31 of 47 (66%) countries identified low rates of CP resistance among E. coli ( > 5% in only one country); for Klebsiella spp., rates of CP resistance exceeded 5% in only 2 nations (13%) 137 . In a study of 292 clinical isolates of Enterobacteriaceae from two hospitals in Nigeria between January and June 2019, 129 (44.2%) were resistant to 3 rd -generation cephalosporins but only 19 (6.5%) were CRE 138 . Only 7 of 19 (36.8 %) CRE isolates produced CPases; genotypes included NDM-5 (n=5) and OXA-181 (n=2), respectively.…”
Section: Africamentioning
confidence: 99%
“…com) [19]. Codon-code aligner version 9.0.1 was used to obtain contig sequences [20]. The contig sequences were compared to the reference 16S rRNA sequences at National Center for Biotechnology Information (NCBI) database by using Basic Local Alignment Search Tool (BLAST) algorithm.…”
Section: Molecular Identificationmentioning
confidence: 99%